Spatial Hearing by Bilateral Cochlear Implant Users With Temporal Fine-Structure Processing - Ausili, Sebastián A.; Agterberg, Martijn J. H.; Engel, Andreas; Voelter, Christiane; Thomas, Jan Peter; Brill, Stefan; Snik, Ad F. M.; Dazert, Stefan; Van Opstal, A. John; Mylanus, Emmanuel A. M. (Frontiers in Neurology, 2020)
Several studies have demonstrated advantages of bilateral versus unilateral cochlear implantation in listeners with bilateral severe to profound hearing loss. However, it remains unclear to what extent bilaterally implanted listeners have access to binaural cues, e.g. accurate processing of interaural timing differences (ITDs) for low-frequency sounds (<1.5 kHz) and interaural level differences (ILDs) for high-frequencies (>3 kHz). We tested 25 adult listeners, bilaterally implanted with MED-EL cochlear implant (CI) devices, with and without fine-structure (FS) temporal processing as encoding strategy in the low-frequency channels. In order to assess whether the ability to process binaural cues was affected by fine-structure processing, we performed psychophysical ILD and ITD sensitivity measurements, and free-field sound-localization experiments. We compared the results of bilaterally implanted listeners with different numbers of FS channels. All CI listeners demonstrated good sensitivity to ILDs, but relatively poor to ITD cues. Although there was a large variability in performance, some bilateral CI users showed remarkably good localization skills. The FS coding strategy for bilateral CI-hearing did not improve fine-structure ITD processing for spatial hearing on a group level. However, some CI listeners were able to exploit weekly informative temporal cues to improve their low-frequency spatial perception.